Determinan Selfcare Management Hipertensi pada Pegawai Negeri Sipil Kementerian Kesehatan - Intan Dewi Kumalasari; Syamsulhuda Budi Musthofa; Sutopo Patria Jati (Journal of Telenursing (JOTING), 2023)
This study looks at the determinants related to self-care management of hypertension in Civil Servants of the Ministry of Health. The research method used is quantitative with a cross-sectional approach and the logistic regression analysis method. The research results showed that most respondents (51.9%) were female, and the majority (53.1%) had insufficient self-care management for hypertension. Age, perceived benefits, perceived barriers, and health promotion in the workplace have a significant relationship with self-care management of hypertension, with perceived barriers as the most dominant factor (p = 0.000, OR = 6.869). In conclusion, there is a need to increase health promotion in the workplace to reduce perceived barriers and increase perceived benefits for self-care management of hypertension. Keywords: Civil Servants (PNS), Perceived Barriers, Health Promotion, Selfcare Management